The Effect Of The Problem Based Learning (Pbl) Model On Students' Mathematics Problem Solving Ability In Comparison Of Class Vii Smp Private Pab 1 Klumpang - Arni, Nina; Nasution, Marah Doly (AlAdzkiya International of Education and Sosial (AIoES) Journal, 2021)
This study aims to determine how the effect of the Problem Based Learning (PBL) model on students' mathematical problem solving abilities in the Comparison material for class VII Private Junior High School PAB 1 Klumpang in the 2020/2021 academic year. The instrument used in this research is a mathematical problem solving ability test in the form of a description, with the material being taught is a comparison. The subjects in this study were seventh grade students of PAB 1 Klumpang Private Junior High School, while the sample in this study consisted of two classes. One class is the experimental class and the other is the control class. The sample in the experimental class amounted to 30 people, and the sample in the control class also amounted to 30 people. From the data analysis using simple regression test, the average test of mathematical problem solving ability in the experimental class before and after learning was 73.33 and 83.83. While the average control class math problem solving ability test before and after learning was 74.17 and 75.5. Hypothesis testing in this study used the r-test, which was conducted to determine the level of students' mathematical problem solving abilities before and after being taught using the Problem Based Learning (PBL) learning model. If > then it can be concluded that there is an effect of Problem Based Learning (PBL) learning model on students' mathematical problem solving abilities. After the calculation, the score on the mathematical problem solving ability of experimental class students is 0.722 while the value is 0.361, so it can be seen that > . Thus, it can be concluded that there is an effect of the Problem Based Learning (PBL) learning model on students' mathematical problem solving abilities in the Comparison material for class VII Private Junior High School PAB 1 Klumpang in the 2020/2021 academic year.